2020
DOI: 10.1180/mgm.2020.72
|View full text |Cite
|
Sign up to set email alerts
|

Kagomé networks of octahedrally coordinated metal atoms in minerals: Relating different mineral structures through octahedral tilting

Abstract: Kagomé nets of corner-connected triangles of atoms occur in diverse minerals, from the {111} anion arrays in perovskite-group minerals to natural metallic alloys like auricupride, AuCu3, to the cation layers in atacamite-group minerals. We review here two- and three-dimensional kagomé networks in minerals where the kagomé node atoms are octahedrally coordinated in hexagonal tungsten bronze (HTB) arrays. Octahedral tilting, coupled with capping of the apical anions of the triangular groupings of octahedra in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…In contrast to aldermanite, which has the large 8-coordinated Na + cation occupying the centres of the hexagonal rings in the HTB layers, the zirconolite-3 O minerals have small cations displaced from the centres of the hexagonal rings to take up 4- and 5-coordination. The zirconolite-3 O mineral structures, with sawtooth-like intersecting kagomé nets of small cations, are topologically distinct from the structures of other zirconolite minerals, zirconolite-2 M and zirconolite-3 T , which have planar kagomé nets of small cations (Grey, 2020). As a result, it is debatable if zirconolite-3 O should be classed as a zirconolite polytype.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to aldermanite, which has the large 8-coordinated Na + cation occupying the centres of the hexagonal rings in the HTB layers, the zirconolite-3 O minerals have small cations displaced from the centres of the hexagonal rings to take up 4- and 5-coordination. The zirconolite-3 O mineral structures, with sawtooth-like intersecting kagomé nets of small cations, are topologically distinct from the structures of other zirconolite minerals, zirconolite-2 M and zirconolite-3 T , which have planar kagomé nets of small cations (Grey, 2020). As a result, it is debatable if zirconolite-3 O should be classed as a zirconolite polytype.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, electron microprobe (EMP) analysis on the Tom's quarry sample showed significant quantities of Na and F that were not analysed for by Harrowfield et al (1981) although they did report that Na was detected in a qualitative EMP scan. A crystal structure determination revealed that aldermanite contains unusual sawtooth-like layers of octahedrally coordinated Al that can be described as intersecting kagomé layers (Grey, 2020). Such layers have been reported recently in the chemically diverse minerals of the walentaite group (Grey et al , 2020) and the zirconolite group (Chukanov et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The doubling seems to be caused by both out-of-center displacements of the W atoms in their oxygen octahedra due to the second-order Jahn-Teller (SOJT) effect for the d 0 cations 68 and tilting the cornersharing octahedra along the doubled axis, which are often observed in HTB and related tungsten oxides. 69,70 Obviously, these effects lead to disordering of the tungsten and oxygen atoms in our average structural models of the HTB-like polytungstates and diffuse scattering in their crystals, which may indicate displacive or order-disorder phase transitions observed in A 4 W 11 O 35 (A = Rb, Cs) 71 and many HTB-related tungsten oxides. [72][73][74][75] Discrepancies in the lattice dimensions and symmetry of the HTB-like polytungstates (Table 4) can also be caused by forming various superstructures (including metastable ones) at such phase transitions.…”
Section: Crystal Chemistry and A Homologous Series Of Layered Htb-lik...mentioning
confidence: 91%
“…8b). A trigonal-prismatic environment is considerably rarer than octahedral (Housecroft and Sharpe 2004), but is observed for elements such as for Sb in pyrochlore minerals like roméite (Grey 2020) The presence of water in synthetic montanite (SynCeramic) is somewhat surprising as the montanite crystals were the product of a ceramic reaction performed at high temperatures. We hypothesise that the water is either incorporated into the structure upon cooling and exposure to moisture in the atmosphere or, most likely, during the leaching process.…”
Section: Structure Description and Comparisonmentioning
confidence: 99%